SpongeBob SquarePants. The complete sixth season [videorecording (DVD)] - Kenny, Tom, 1962-; Fagerbakke, Bill, 1957- (Paramout Home Entertainment, 2012)
Join in on all the fun with Spongebob, Patrick, Gary, and all the gang.